2019
DOI: 10.1051/0004-6361/201834087
|View full text |Cite
|
Sign up to set email alerts
|

Mergers, tidal interactions, and mass exchange in a population of disc globular clusters

Abstract: Globular clusters (GCs), the oldest stellar systems observed in the Milky Way, have for long been considered single stellar populations. As such, they provided an ideal laboratory to understand stellar dynamics and primordial star formation processes. However, during the last two decades, observations unveiled their real, complex nature. Beside their pristine stars, GCs host one or more helium enriched and possibly younger stellar populations whose formation mechanism is still unknown. Even more puzzling is th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…A large spread in metallicity alone can be explained by self-enrichment during formation (Bailin 2018), but it does not explain the large spread in age. Thus, we suggested that this could be the result of a merger event between two or more clusters that fell into the central region of the host, as suggested through simulations (e.g., Amaro-Seoane et al 2013;Gavagnin et al 2016;Bekki & Tsujimoto 2016;Khoperskov et al 2018;Mastrobuono-Battisti et al 2019a). In addition, a contribution to this high spread in metallicity might be due to the old, metal-poor population of Sgr dSph that mixed with the merged GCs to the resulting OMP population of this NSC.…”
Section: Omp: Remnant Of a Cluster Merger?mentioning
confidence: 62%
See 2 more Smart Citations
“…A large spread in metallicity alone can be explained by self-enrichment during formation (Bailin 2018), but it does not explain the large spread in age. Thus, we suggested that this could be the result of a merger event between two or more clusters that fell into the central region of the host, as suggested through simulations (e.g., Amaro-Seoane et al 2013;Gavagnin et al 2016;Bekki & Tsujimoto 2016;Khoperskov et al 2018;Mastrobuono-Battisti et al 2019a). In addition, a contribution to this high spread in metallicity might be due to the old, metal-poor population of Sgr dSph that mixed with the merged GCs to the resulting OMP population of this NSC.…”
Section: Omp: Remnant Of a Cluster Merger?mentioning
confidence: 62%
“…The final rotation of two merged clusters strongly depends on the conditions, as the orbital configuration and relaxation states of the merging clusters do not always result in a highly rotating structure (Mastrobuono-Battisti et al 2019a). Based on the kinematics, we cannot be certain that two merging clusters were actually involved in the formation of the OMP population but cannot discard this possibility either.…”
Section: Omp: Remnant Of a Cluster Merger?mentioning
confidence: 99%
See 1 more Smart Citation
“…In this figure, GCs appear as density peaks of the stellar distribution, embedded in a low-density field of stars escaped from the clusters over time. This loss of stellar mass from the clusters is the consequence of the action of the galactic gravitational field and of the mutual gravitational interactions among GCs, as we will discuss in more detail in Mastrobuono-Battisti et al (2018). The effect of the galactic tidal field is also responsible for generating extended tidal tails around clusters, which are probes -on large scales -of the GC orbits (Montuori et al 2007).…”
Section: Evolution Of An N-body System Of Disc Gcs: Resultsmentioning
confidence: 97%
“…Therefore, for the accreted populations, distance from the GC centre increases with their decreasing mass. For the longterm evolution of these accreted populations in the host GC we refer to Mastrobuono-Battisti et al (2018). In the following, we describe in more detail the mergers and mass exchanges taking place in our simulated GC system.…”
Section: Major Mergers and Mass Accretionsmentioning
confidence: 99%